THE FIDUCIARY RELATIONSHIP BETWEEN A COMPANY AND ITS DIRECTORS - Lindi Coetzee; Jan-Louis van Tonder (Obiter, 2014)
The fiduciary relationship that exists between a company and its directors is a universal concept. Section 5(2) of the Companies Act 71 of 2008 provides that, to the extent appropriate, a court interpreting or applying the provisions of the 2008 Act may consider foreign company law. This article examines the meaning of the word “fiduciary”, when a fiduciary relationship comes into existence, the characteristics of a fiduciary relationship, the meaning of the term “director”, different “types” of directors and discusses to whom the duties are owed. The nature of the fiduciary relationship in Australia and the State of Delaware in the United States of America is briefly compared with that of South Africa to identify similarities and differences. The research proposes a set of characteristics that can be considered when deciding whether a fiduciary relationship exists. The article does not propose that the set of characteristics identified must constitute a numerus clausus.